Definition of the Right Freely to Choose among Products and Services - Fuentes Véliz, Juan Andrés (2017)
This scholarly article addresses the right to choose freely among products and services, contained in the Code of Consumer Protection and Defense and recognized from the origins of this specialized field of law. We study the content of this right, based on a comparative analysis. All rights have limits and this right is not the exception. Therefore, we precise them.